Strategic asylum law making in Europe: institutional locus - Jenny Monheim (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2007)
Given the background of changing institutional competencies in the European Union, we analyze the choice of asylum law standards of national and European parliaments, the Council of the European Union and codecision between the Council and the European Parliament. In a two country model we nd that the European arrangements maximize neither the welfare of the Member Countries nor the welfare of refugees. For the latter, there has been an improvement in the institutional location of asylum law making with the introduction of codecision. The current development towards a Common European Asylum System is in the interest of neither party.
Keywords: D72; D78; F22; K42; H53; 330; Asylum policy; Illegal immigration; Regulatory competition; Public choice; EU institutions